Prostate Cancer - Scott Eggener (The Scientific World Journal)
Prostate cancer continues to be a significant public health issue worldwide, particularly in countries where men have life expectancies long enough to clinically manifest the disease. In many countries, it remains one of the leading causes of cancer-related morbidity and mortality.